2016
DOI: 10.1177/1053815116668643
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic Reading

Abstract: Dialogic reading is an evidence-based practice for preschool children who are typically developing or at-risk; yet there is limited research to evaluate if it has similar positive effects on the language and preliteracy skills of children with disabilities. This quasi-experimental study examined the effects of dialogic reading, with the incorporation of pause time, on the language and preliteracy skills of 42 preschool children with disabilities. Following random assignment of students at the classroom level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 34 publications
(60 reference statements)
0
14
0
1
Order By: Relevance
“…There was an immediate change in level after the first intervention session which was maintained across all three intervention tiers, suggesting that the DR approach provided the scaffolding that Arjun needed to access and comprehend the text. Although there has already been ample evidence that DR is a successful strategy to use for students with disabilities (Fleury & Schwartz, 2017; Morgan & Meier, 2008; Rahn et al, 2016; Towson et al, 2016) and emergent readers (Chlapana, 2016; Cohrssen et al, 2016; Huennekens & Xu, 2016; Maine, 2013; Pillinger & Wood, 2014), there are few studies that explore DR with deaf readers, and none on how DR may improve deaf readers’ comprehension. The current data, though insufficient to draw general conclusions, suggest DR can be successful in this context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was an immediate change in level after the first intervention session which was maintained across all three intervention tiers, suggesting that the DR approach provided the scaffolding that Arjun needed to access and comprehend the text. Although there has already been ample evidence that DR is a successful strategy to use for students with disabilities (Fleury & Schwartz, 2017; Morgan & Meier, 2008; Rahn et al, 2016; Towson et al, 2016) and emergent readers (Chlapana, 2016; Cohrssen et al, 2016; Huennekens & Xu, 2016; Maine, 2013; Pillinger & Wood, 2014), there are few studies that explore DR with deaf readers, and none on how DR may improve deaf readers’ comprehension. The current data, though insufficient to draw general conclusions, suggest DR can be successful in this context.…”
Section: Discussionmentioning
confidence: 99%
“…This multiple baseline across content probe design study focused on vocabulary acquisition rather than type of comprehension question responses and did not find these same carryover effects (Trussell & Easterbrooks, 2014). In fact, a majority of studies of DR measure vocabulary acquisition rather than comprehension as the primary outcome among children with disabilities or who are deaf (Fung et al, 2005; Morgan & Meier, 2008; Rahn et al, 2016; Towson et al, 2016; Trussell and Easterbrooks, 2014) and did not find similar effects. There are a couple of possibilities as to why these effects occurred in this study, which are explored below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this study, the students were placed in small groups of three to five and pulled from regular classroom activities during dialogic reading activities and then returned afterwards. The study demonstrated positive results (Towson, Gallagher & Bingham, 2016).…”
Section: Dialogic Reading Strategiesmentioning
confidence: 77%